Działalność Ochotniczych Straży Pożarnych w gminie Zielona Góra = Activities of volunteer fire brigades in Zielona Góra commune - Nijaki, Ireneusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Volunteer Fire Brigades in Zielona Góra Commune are specialized, well-educated, designed and prepared units to realize the tasks associated with the rescue and firefighting services, with over 400 people participating in the activities. Along with the rescue and firefighting services, the Volunteer Fire Brigades conduct fire prevention trainings and play the culture-forming role bringing up, educating and integrating the inhabitants of the commune. The article presents the detailed quantitative data of Volunteer Fire Brigades in Zielona Gora Commune.
Keywords: Zielona Góra (okręg); Ochotnicza Straż Pożarna; gmina